ANALISIS PENGARUH PENINGKATAN INTERFERENSI MS USER LAYANAN SUARA, DATA DAN VIDEO PADA SISTEM MULTISEL TERHADAP BESARNYA KAPASITAS HOME CELL DENGAN ARAH REVERSE LINK PADA SISTEM CDMA - Santoso, Gatot (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2015)
The future technology of the technology of wireless communication system must be able to serve a multimedia application, included voice, data, and high speed video information. CDMA is one of the communication technology which can be used and have been proved as a technique of multiple access that capable of provide this service requirement. In this system the multicell is analyzed until two tier and the system of multiclass is divided into three classes of traffic which are class 1 for voice, class 2 for data, and class 3 for video services. The analysis of capacity is done according to the effect of variable quality of services, chip rate, bit rate and activity factor. The result show that higker chip rates can maintain the required BER of each information and achieve the user capacity in high traffic condition. However, larger bit rate will decrease total capacity. Furthermore larger activity factor will decrease total capacity of system. So the effect of interference in multi cell system can decrease home cell capacity of offered information traffics.